AUDIT KOMUNIKASI INTERNAL MEDIA SOSIAL HUMAS PEMERINTAH KABUPATEN TEGAL - Oka Imanidar; Agus Ganjar Runtiko; Shinta Prastyanti (Kinesik, 2023)
Social Media has become a significant communication tool in conveying information to various parties, including government employees and the general public. In this context, this study aims to audit the internal communication of social media conducted by Public Relations Tegal Regency government. This study uses qualitative research methods involving content analysis of messages delivered through social media, as well as interviews with public relations staff to understand the strategy and objectives of internal communication. The results of this audit provide a comprehensive overview of the effectiveness of internal communication campaigns through social media. These findings can provide valuable input to the Public Relations of the Tegal Regency government in improving its internal communication strategy. The identified potential obstacles and opportunities can be used as a basis for formulating better communication plans in the future. Social media internal communication Audit is a crucial step in ensuring that government messages can be conveyed clearly, accurately, and effectively to various stakeholders. By utilizing the results of this audit, the Tegal Regency government can strengthen internal communication through social media, thus creating a better understanding of government policies, programs, and initiatives among employees and the community.